INFLUENCE OF ARBUSCULAR MYCORRHIZAL FUNGI ON PLANT GROWTH PROMOTION AND BIOLOGICAL CONTROL OF VERTICILLIUM WILT OF TOMATO (LYCOPERSICON ESCULENTUM). - SATYA VANI MOTHA; HINDUMATHI AMBALLA; NARASIMHA REDDY BHUMI (International Journal of Pharma and Bio Sciences, 2014)
Tomato (Lycopersicon esculentum Mill) is an important vegetable crop and is known as productive as well as a protective food because of its therapeutic values. Arbuscular mycorrhizal fungi are known to enhance plant growth mainly through nutrient uptake. Indigenous arbuscular mycorrhizal fungi Glomus fasciculatum (Thaxt.) Gerd. & Trappe, was inoculated in field conditions using three different cultivars of tomato viz., PKM-1, Gaurav and Monarch. Various morphological parameters, nutrient levels and disease incidence were evaluated. A significant increase in shoot and root leaf lengths, shoot and root fresh, dry weights, biomass, dry matter production and nutrient levels NPK were recorded in AM fungi treated plants over controls. There was a maximum reduction of disease incidence by 53.18% in Monarch cultivar in the plants inoculated with AM fungi in combination with the pathogen Verticillium dahliae compared to only pathogen inoculated plants. This was followed by 49.55% and 45.48% in Gaurav and PKM-1 cultivars respectively. All the three cultivars have shown positive response to Glomus fasciculatum recording significant increase in plant growth and reduction in percentage of disease incidence.